Absolute Power in the Dimensions of Indonesian Law - Masitah Pohan (International Journal Reglement & Society (IJRS), 2022)
The granting of power of attorney is the most common legal act in society, besides that the granting of power of attorney is a very basic and important act in the process of legal and non-legal relations, in the event that a person wishes to be represented by another person to become his/her proxy, to carry out everything that is required of him/her. is in the interests of the authorizer, in all respects, including in relations with parties other than the proxy. the intent and purpose of the granting of power as regulated in Article 1795 of the Civil Code has shifted. As for the shift in question, are the limitations set out in Article 1796 of the Civil Code which states that the granting of power only covers administrative actions, and Article 1797 of the Civil Code which also states that power is not allowed to do anything. which exceeds his power, does not always have to be heeded, as well as other limitations, namely Article 1813 of the Civil Code concerning the expiration date of the grant of power of attorney. And this shift is what the power-giving agency calls absolute power.